A quick study on SRL profiles of online learning participants during the anticipation of the spread of COVID-19 - Dwi Sulisworo; Nur Fatimah; Septi Shinta Sunaryati; Sanidi Sanidi; Dwi Sulisworo (International Journal of Evaluation and Research in Education (IJERE), 2020)
The spread of the COVID-19 coronavirus occurs in all countries. This pandemic incident has been taken seriously by various sectors including in the world of education. This research is a quantitative descriptive study to explain the Self-Regulated Learning (SRL) profile of Indonesian students in online learning which is carried out in COVID-19 emergencies. The research commenced three days after the establishment of the WHO COVID-19 pandemic. The respondents were taken by accident sampling at several schools implementing online learning after the designation of this mode by the Indonesian Ministry of Education and Culture on March 15, 2020. The schools comprised general high schools and vocational schools. The data were collected via Google Form filled out by 10th to 12th-grade students. The instrument used was a questionnaire with a scale of 1 to 5 (from absolutely disagree to absolutely agree) consisting of planning, monitoring, controlling, and reflecting aspects. There were two analytical techniques used i.e., descriptive statistics and ANOVA. The results of this study indicate that students in Indonesia still need assistance and mentoring from teachers to improve SRL. Several mentoring strategies can be applied to manage active learning. The teachers should explicitly include the process of mentoring, strengthening the students’ SRL. Teachers need to be aware that online learning is not only to master certain subject matters but also to strengthen SRL.